Neuro-Fuzzy techniques for intelligent information systems - Kasabov Nikola; Kozma Robert (Heidelberg Physics-Verlag, 1999)
Comprises selected papers covering contemporary issues of the development and the application of neuro-fuzzy techniques. The volume has four main parts. Part one presents generic techniques and theoretical issues while part two, three and four deal with
Keywords: Expert systems(Computer science); Fuzzy systems; Neural networks(Computer science)